Pemasangan Convex Mirror di kawasan Jalan Pariwisata Desa Girimukti Penajam Paser Utara - Irna Hendriyani; Aldi Adrian Sianturi; Jeremmy Makatuuk; Maslina Maslina (Abdimas Universal, 2023)
The aim of installing convex mirrors is to reduce the number of accidents that occur on Tourism Road. This road is busy with users on weekends and holidays because it is the access to the beach tourism in Girimukti Village Penajam Paser Utara. Convex Mirrors or convex mirrors are additional equipment on roads that function as a tool to increase the visibility of motor vehicle drivers. These convex mirrors are generally installed on the edge of the road in locations where the view of motor vehicle drivers is very limited or obstructed, especially at sharp bends. In this activity, convex mirrors were installed at three points on the Girimukti Penajam Paser Utara Village Tourism Road. The installation point was determined after coordinating with Bhabinkamtibmas, Babinsa, Girimukti Village Government and the local RT. From the coordination results, it was determined that one point in RT 5 and two points in RT 11 were the installation points for the convex mirror. The installation was carried out for one day after previously installing the convex mirror components. So when installing, just insert it into the hole that has been prepared. Based on the results of a review after a week of installation, the community felt helped by the presence of this convex mirror, thereby increasing awareness on Tourism Road.